2017
DOI: 10.1093/bja/aex196
|View full text |Cite
|
Sign up to set email alerts
|

Variations in assessment and certification in postgraduate anaesthesia training: a European survey

Abstract: Assessment and certification processes in European anaesthesia training are diverse. In many countries, a time-based apprenticeship model is evolving towards a competency-based certification process. This diversity precludes comparison of competence of graduating anaesthetists across Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…16 A survey of anaesthesia training in the USA, UK, Canada, Japan, Denmark, and Switzerland showed that, whilst the surveyed countries purported to adhere to competency-based curricula, they had quite different structures and training programmes. 17 Similar findings were reported in a survey of 36 European countries, 18 with concerns that variable anaesthesia training in Europe resulted in variable graduate outcomes and a potentially detrimental effect on regional standards.…”
Section: Developing a Consensus On An Achievable Cbme Curriculumsupporting
confidence: 69%
“…16 A survey of anaesthesia training in the USA, UK, Canada, Japan, Denmark, and Switzerland showed that, whilst the surveyed countries purported to adhere to competency-based curricula, they had quite different structures and training programmes. 17 Similar findings were reported in a survey of 36 European countries, 18 with concerns that variable anaesthesia training in Europe resulted in variable graduate outcomes and a potentially detrimental effect on regional standards.…”
Section: Developing a Consensus On An Achievable Cbme Curriculumsupporting
confidence: 69%
“…The present study has identified some major inconsistencies in the types of assessments used, both for summative and formative assessment in respiratory medicine training. Similar variability across Europe was recently reported for anaesthetic training [15]. There are a number of deficiencies in our study: it is incomplete, sampling only just over half of the target respondents, although it has information from 73% of the target countries, representing 88% of the population.…”
Section: Discussionmentioning
confidence: 69%
“…The introduction of an OSCE to the clinical component follows the international trend towards a more competencybased certification process. 12 To our knowledge this will be the first postgraduate orthopaedic surgery exit examination in Africa to include an OSCE as part of the certifying process. Currently the essay-style questions are in a process of being phased out of the written component of the FC (Orth)SA final examination and have been replaced by the more reliable and reproducible MCQ format.…”
Section: Discussionmentioning
confidence: 99%